ISOLATION AND PURIFICATION OF APIGENIN FROM ALLIUM FISTULOSUM - V., TEENA MAGLINE IMMACULATE; P., SHLINI; H., MARY CLARE (International Journal of Current Pharmaceutical Research, 2020)
Objective: The objective of this study is to optimize the extraction of apigenin (4′, 5, 7-trihydroxy-flavone) from Allium fistulosum. Methods: The present study aims at extracting flavonoids from the plant using methanol as a solvent. Phytochemical screening was performed to analyse the phytochemical constituents present in the extract. Apigenin was isolated from the leaves of A. fistulosum and further purified and identified by TLC and HPLC. Results: Phytochemical screening showed the presence of various constituents like terpenoids, tannins, flavonoids, reducing sugars, phenolics, cardiac glycosides and amino acids. TLC results indicated the presence of apigenin in the plant extract with the Rf value of 0.88, which coincided with the standard apigenin of Rf value 0.83. HPLC results showed a similarity in the peak of 17.1 min of the standard with the minor peak of 17.324 min of the sample. This proved the presence of apigenin in low quantities. Conclusion: This present study suggests that Allium fistulosum can be a moderate source of apigenin. This compound was isolated for the first time from this plant.